Circadian Typology and Emotional Intelligence in Healthy Adults - Antúnez-Vílchez, Juan Manuel; Navarro-Humanes, José Francisco; Adan, Ana (Taylor & Francis, 2013)
Several aspects related to health, such as satisfaction with life, perceived well-being, and psychopathological symptomatology have been associated with circadian typology and with emotional intelligence. Nevertheless, the relationships between circadian typology and emotional intelligence have not been explored yet. The purpose of the present study is to examine the relationships between circadian typology and emotional intelligence, taking into account the possible interactions between sex and physical exercise, and controlling for age. A sample of 1011 participants (649 women), aged between 18 and 50 yrs (26.92 ± 6.53) completed the reduced Morningness-Eveningness Questionnaire (rMEQ) and the Trait Meta-Mood Scale-24 (TMMS-24). The TMMS-24 considers three dimensions of emotional intelligence: emotional attention, emotional clarity, and emotional repair. Women showed higher values for emotional attention, whereas men showed higher values for emotional repair (p < 0.035, in both cases). Subjects who do physical exercise weekly showed higher values for emotional repair (p = 0.001) regardless of circadian typology or sex. Circadian typology presents differences in all scores of emotional intelligence dimensions. Morning-type had lower emotional attention than evening- and neither-type; neither-type had lower emotional repair than morning-type, and lower emotional clarity than both evening- and morning-type (p < 0.046, in all cases). Moreover, circadian typology modulated the sex differences in emotional attention, and only morning-type men showed a low emotional attention score. From the results of emotional intelligence we can conclude that morning typology may be a protective factor in terms of general health, whereas we should be aware that the neither-type may present a possible vulnerability to develop psychological problems.
Keywords: Ritmos circadianos - Aspectos psicológicos; Circadian typology; Emotional intelligence; Morningness-eveningness